Etika Profesi Bimbingan dan Konseling: Menghadapi Tantangan Kerahasiaan dalam Layanan Konseling Online - Anindya, Jovita; Budiman, Nandang; Nadhiroh, Nadia Aulia (Indonesian Journal of Educational Counseling, 2024)
Rapid changes in the world of education triggered by technological advances have stimulated interest in the use of online counseling as a method of mental health services. The COVID-19 pandemic has also accelerated the shift to online counseling as a primary option. The research results show that online counseling has equivalent effectiveness to face-to-face counseling. However, there are a number of ethical issues that need to be considered in online counseling practices, especially those related to the confidentiality and security of client data. Efforts to maintain confidentiality are a priority, including the use of secure technology and communication via encrypted platforms. Counselors need to understand the potential risks involved and continually increase their knowledge of online counseling ethics. This study used a systematic literature review (SLR) approach to investigate the development of online counseling practices and related ethical issues. In Indonesia, ABKIN has not yet issued standard guidelines for counseling services via the internet, so this is a challenge in maintaining client confidentiality in this country.